Motion planning for a quadruped robot in heat transfer tube inspection - Li, Jiawei; Liu, Zhaojin; Li, Sicen; Jiang, Jikai; Li, Yuxiao; Tian, Changda; Wang, Gang (Automation in construction, 2024)
Steam generators (SGs) are essential in nuclear power facilities and require regular inspection to maintain their safety and operational effectiveness. This paper presents a quadruped robot designed to inspect SG heat-transfer tubes. The point-to-point crawling-motion planning problem of the robot is addressed by integrating an improved A* algorithm with an offline motion-posture library established for the tube-sheet environment. The planner can provide the global path, the step size for each crawling cycle, and the strategic placement of footholds. The proposed method can facilitate the robot in navigating obstacles on a tube sheet, seamlessly adapt to various postures and step lengths, and eliminate the necessity for turning or superfluous posture adjustments, thereby ensuring crawling efficiency. The efficacy of the proposed planner is validated rigorously through simulations and experimental trials using an actual SG tube sheet. •A quadruped robot designed for inspecting heat transfer tubes.•A robot motion posture library tailored to tube sheet environments.•An enhanced A* algorithm for the motion planning.•Experiments were conducted on an actual SG tube sheet.